Spin reorientation and glassy dynamics in La(1.55)Sr(0.45)NiO(4) - Giblin, SR; Freeman, P; Hradil, K; Prabhakaran, D; Boothroyd, A (2008)
The magnetism of charge-stripe-ordered La1.55Sr 0.45NiO4 was studied by a combination of neutron diffraction, muon-spin relaxation (μSR), and bulk susceptibility. Long-range magnetic ordering was observed at a lower temperature by μSR than by neutron diffraction, consistent with a glassy transition to the ordered phase. A second magnetic transition is detected by all techniques and is consistent with a spin reorientation. On cooling below TSR=42 K the spins reorientate from lying 32.9±0.6° away from the stripe direction at 70 K to 56.8±0.4° at 10 K. The magnetic order was observed by neutron diffraction to have both three-dimensional and two-dimensional (without any correlation along the c axis) characters. μSR measurements confirmed this and are consistent with a single magnetically ordered spin-stripe phase. The effects of checkerboard charge order on the ordered phase and the characteristics of the phase diagram of the spin reorientation in charge-ordered La2-xSrxNiO4 are commented on. © 2008 The American Physical Society.